Implementation of Articulate Storyline to Improve Students’ Interest in Learning Islamic History Lesson - Khozin, Khozin; Haris, Abdul; Rozza, Dian Silvia (Jurnal Tarbiyatuna, 2023)
Inadequate educational ability shown by educators and resources as well as the limited time is the factor that causes inadequate student’s understanding. One of the approaches to decrease the problem involves the use of various instructional resources. The objective of this research is to analyze the design of media with clear storyline and characteristics that determine the level of students’ interest in their education. This research uses qualitative approach with case study. Observation, interview, and documentation are the main method used in the process of data collection. Before, in the middle of, and after learning experience with media, observations were done. Text books and media made in Articulate Storyline are the documentation used. To analyze the data, first, the data must be summarized, then presented, and last, concluded Based on the finding of the research, the most basic step to be done in the process of the making of the media is examining the concept and the design of the media end-to end. It is done in order to make Articulate Narrative media in the lecture of Islamic History as easy as possible. Besides that, the design must be modified to accommodate various demands and students’ ways of study. There are internal and external factors that play roles in determining the level of a student’s learning interest. The use of Articulate Storyline, which is an innovative learning media, is an example of an extrinsic element which has potential to help students develop their learning interest.